Blaski i cienie historii Muzeum Sztuki Kościelnej na Zamku Poznańskim - Pudelska, Aleksandra (Ecclesia. Studia z Dziejów Wielkopolski, 2014)
The paper focuses on the history of the Museum of Ecclesiastical Art at the Imperial Castle in Poznan. It functioned between 1923 and 1929, being a short episode but an important one in the history of the Archdiocesan Museum in Poznań. Formerly a Diocesan Museum, it was established in 1898 with an exquisite collection of sacred art assembled over the years. However, due to the lack of exhibition space the collection was only stored and not many people knew about it. Shortly after Poland regained its independence, Poznan's elite wanted to partially convert the imperial castle (built by the Prussians for William II, German Emperor) into a museum of Polish art. The Government asked the Church to deposit their art collection and granted the city permission to open the Museum of Ecclesiastical Art at the Imperial Castle in Poznan. The proposition was accepted. The two people nominated to carry out this enterprise were: Rev. Edmund Majkowski, the museum's director, and Mr. Nikodem Pajzderski, art conservation official. With great effort they created a very interesting exhibition. Unfortunately, the Government did not show much interest in the newly opened museum and did not fulfill its promises. Investments were close to nothing and with time the whole project was abandoned and the collection removed from the castle.